Frailty and sarcopenia in combination are more predictive of mortality than either condition alone. (February 2021) - Thompson, Mark Q.; Yu, Solomon; Tucker, Graeme R.; Adams, Robert J.; Cesari, Matteo; Theou, Olga; Visvanathan, Renuka
Highlights: 2.8 % of participants were both frail and sarcopenic, 15.5% were frail only, and 3.5% were sarcopenic only. Classification as both frail and sarcopenic resulted in significantly elevated mortality risk: adjusted HR = 3.52. Frail individuals should also be screened and assessed for sarcopenia, and vice versa, and offered appropriate intervention. Abstract: Background: Frailty and sarcopenia are age-related conditions with shared features and are both associated with adverse health outcomes. Relatively little is known about outcomes of these conditions in combination. The aim of this study was to examine the predictive ability of combined frailty and sarcopenia classification on mortality. Methods: Frailty was measured in 716 community-dwelling adults aged ≥65 years from the North West Adelaide Health Study (mean age 74.1(6.1) years, 55.5 % female) using the frailty phenotype (FP) and sarcopenia using the revised consensus definition from the European Working Group on Sarcopenia. Participants were classified as: neither frail nor sarcopenic, frail-only, sarcopenic-only, or both frail and sarcopenic. All participants had a minimum of 10 years of mortality follow-up. Results: We identified 2.8 % of participants as both frail and sarcopenic, 15.5 % as frail-only, and 3.5 % as sarcopenic-only. Classification as both frail and sarcopenic, in a multivariable model, resulted in significantly elevated mortality risk (HR = 3.52, p < .001), which was over three times that of those neither frail nor sarcopenic. Frail-only was also a significant mortality predictor (HR = 2.03, p = .001), while classification as sarcopenic-only was not a significant predictor of mortality (HR = 1.65, p = .141). There was no significant difference in severity of frailty (mean number of characteristics) or grip strength between frail-only and those with both conditions when stratified by sex. Conclusions: Individuals identified as frail would benefit from screening and assessment for sarcopenia, and vice versa for those identified as sarcopenic, as the mortality risk for individuals with these conditions in combination is nearly double that of each separately.